Ø¹Ù„Ø§Ù‚Ø© Ø¨ÙŠÙ† ØÙØ¸ Ø§Ù„Ù‚Ø±Ø§Ù† ÙˆÙ†ØªØ§Ø¦Ø¬ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ø¬Ø§Ù…Ø¹Ø© Ù‡Ø§Ø´Ù… Ø£Ø´Ø¹Ø±ÙŠ (Ø¯Ø±Ø§Ø³Ø© ÙƒÙ…ÙŠØ© ÙÙŠ Ù…Ø¹Ù‡Ø¯ ÙˆØ§Ù„ÙŠ Ø³ÙˆÙ†Ø¬Ùˆ Ø¬ÙˆÙƒÙŠØ± Ø¯ÙŠÙˆÙŠÙƒ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬) - Iffah Izzati Humairoâ€™; Isniyatun Niswah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
In this article, the purpose of this research is to know the memorization of the Qur'an, to find out the results of learning Arabic, and to find out the relationship between memorizing the Qur'an and learning outcomes in Arabic. Researchers here use quantitative methods with observation, questionnaires, tests and documents. The results of the study: 1) the students there were already very good at reading the Al-Qur'an. But it is better if students read and understand along with its meaning and tartil. 2) Arabic learning outcomes, the average number of answers to the questions is 79. In conclusion, 19 students have the answers above the average, and 2 students whose answers are in accordance with the average, and 14 students have answers below the average. 3) There is a relationship between memorizing the Qur'an and learning Arabic results. This is indicated by the results of the Spearman test with a Sig value of 0.000 <0.05.